Exploring Gen Z Preferences and Perceptions in Digital Banking: A Comparative Insights and Populix National Survey - Eka Putri Nur Asyiam; Sfenrianto (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Digital banking has rapidly transformed financial behavior among young consumers, particularly Gen Z, in Indonesia. This study aims to explore the preferences and perceptions of Gen Z towards digital banking services and to compare them with national trends. A quantitative comparative method was employed, combining survey data from respondents with national Populix survey results. The findings show that SeaBank, blu by BCA, and Bank Jago consistently lead both locally and nationally, confirming their strategic influence on Gen Z’s digital financial behavior. Gen Z in Greater Jakarta prioritizes system quality, including low transfer fees, transaction speed, and ease of navigation, while nationally, information quality, such as promotions, cashback, and security, receives more attention. QRIS is more frequently used for offline transactions, contrasting with national preferences for e-commerce, and personalization features like savings, investments, and AI-driven insights remain underutilized. These results expand the application of the Information System Success (ISS) Model by mapping user preferences and perceptions, highlighting that sustainable digital banking adoption among Gen Z depends on the balance between technical reliability, information quality, and responsive service.